The Use of Computed Tomography… The Use of Computed Tomography in the Diagnosis and Treatment Planning of Temporomandibular Joint Ankylosis in Two Cats - Yavuz, Ü; Yener, K; Doğan, F; Karadağ, MS; Dikmen, K; Hurma, MS; Dusak, A; Hayat, A (Journal of the Hellenic Veterinary Medical Society, 2025)
The use of computed tomography (CT) in the diagnosis and treatment of two cats with a history of inability to open the lower jaw was evaluated. The CT scan of Case 1 revealed extensive callus formation and osseous fusion in the left temporomandibular joint (TMJ) and subluxation in the right TMJ. The CT scan of Case 2 revealed irregular bone proliferations in bilateral intra-articular and periarticular structures. Excision arthroplasty was performed unilaterally in Case 1 and bilaterally in Case 2, and a temporal myofascial flap was applied. At one-year follow-up, both cases maintained painless range of motion of the lower jaw with no signs of re-ankylosis. The CT scanning with three-dimensional (3D) reconstruction is an indispensable imaging method for the diagnosis and preoperative planning of TMJ ankylosis in cats.